Identification of mocroorganism drinking tap water resistant sodium hypochlorite - Рой, И. Ю.; Клименко, Н. А.; Здоровенко, Г. М.; Гончарук, В. В. (WATER AND WATER PURIFICATION TECHNOLOGIES. SCIENTIFIC AND TECHNICAL NEWS, 2015)
The morphological and cultural characteristics of the three dominant bacterial cultures isolated from drinking tap water and water samples at different stages of post-treatment on the installation of water treatment companies of special drinks were studied. From the sequence of the 16S rRNA gene identified the following types of bacteria: Bacillus nanhaiensis, Brevibacterium frigoritolerans and Lysinibacillus fusiformis. It was found that the most resistant to chlorine appeared Lysinibacillus fusiformis. Its resistance to sodium hypochlorite (NaClO) at concentrations of 1.4; 3; 5; and 7 mg / l varies from 1 - 98%, while the duration of exposure of from 5 to 60 minutes, while the remaining two isolates Brevibacterium and Bacillus nanhaiensis frigoritolerans demonstrated lower survival in the presence of NaClO (0 - 16%). A parallel between the morphological type selected bacterial isolates, their ability to form a pellicle at the interface liquid / air and resistant to chlorine is drawn. This resistance to a sufficiently high concentration of sodium hypochlorite may develop as a result of natural selection through random mutation and / or due to the effect of the disinfectant, which can induce the occurrence of acquired resistance.